Having a whale of a time: Linking self-determination theory (SDT), job characteristics model (JCM) and motivation to the joy of gig work - Umer Zaman; Shahid Nawaz; Areesha Javed; Tareq Rasul (Cogent Business & Management, 2020)
The increasing uberization of work has emerged as an intrinsic part of our digitalized society, allowing opportunities for unbridled success for global firms using gig work. The purpose of the present study is to investigate the integrative effect of self-determination and job characteristics on the joy of gig work with the mediating influence of gig worker's motivation (intrinsic and extrinsic). Survey data was collected from 250 gig workers representing two multinational ride-sharing services. The study used partial least squares structural equation modeling (PLS-SEM) technique to empirically test the conceptualized model and hypothesized relationships. The study findings provide empirical evidence to present that joy of gig work is largely affected by gig worker's self-determination and job characteristics. Moreover, gig worker's motivation (intrinsic and extrinsic) significantly mediates the relationship between self-determination and joy of gig work, as well as job characteristics and joy of gig work. This research creates the basis for future investigations that examine the direct and indirect associations between self-determination, job characteristics, motivation, and joy of gig work. The practical implications for global firms include a better understanding of the business value of the joy of work, especially in gig-work environments.
Keywords: 650; Joy of gig work; self-determination theory; job characteristic model; intrinsic motivation; extrinsic motivation